Artikel Review: Pengaruh pH pada Pertumbuhan Bakteri Sesuai Syarat Mutu Obat Tradisional di Indonesia - Ivanny O. Y. Sinaga; Dwie Astrini; Raden B. Indradi (Journal of Pharmaceutical and Sciences, 2023)
Traditional medicine comes from safe ingredients, namely, parts of plants. Based on BPOM No. 32 of 2019, several bacteria are required for the quality of traditional medicines in Indonesia, including Escherichia coli, Clostridia, Salmonella, and Shigella. An optimal pH medium is also needed in the microbial contamination test to produce optimal bacterial growth data. The method used is library search using electronic databases such as Google Scholar and Pubmed with the keywords "Effect of pH on bacterial growth" and other keywords related to microbes and types of bacterial contamination. The inclusion criteria were the sources published in the last ten years, either in English or Indonesian, with exclusion criteria being any sources published that did not discuss the effect of pH on bacterial growth. A total of 24 articles were found, with the final result being 11 articles reviewed. It was found that a difference in pH of at least 0.5 can significantly affect the growth of bacteria.